Foodborne zoonotic trematode infections in Yen Bai, Vietnam: a situational analysis on knowledge, attitude, and practice (KAP) and risk behaviors - Ngan Thi Thuy Phi; Thao Thi Bich Nguyen; Trang Thi Huyen Le; Dung Trung Do; Lenaerts, M.; Losson, B.; Vandenberg, O.; Dorny, P.; Gerven, M. Van; Boere-Boonkamp, M.; Dung Thi Bui (National Institutes of Health, 2022)
Introduction: Foodborne Zoonotic Trematode Infections (FZTi) are neglected tropical diseases of public health concern in Vietnam. The transmission of FZTi is linked to human behavior patterns. The aim was to investigate the knowledge, attitude, and practices regarding FZTi among local people.